1998
DOI: 10.1002/(sici)1098-2396(199806)29:2<105::aid-syn2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Altropane, a SPECT or PET imaging probe for dopamine neurons: II. distribution to dopamine-rich regions of primate brain

Abstract: The dopamine transporter in brain, localized almost exclusively on dopamine neurons, is an effective window on dopamine neurons. SPECT or PET imaging of the transporter in brain requires selective imaging agents that display appropriate pharmacokinetic properties. We previously reported that [125I]altropane ([125I]IACFT,2beta-carbomethoxy-3beta-(4-fluorophenyl)-n-(1- iodoprop-1-en-3-yl)nortropane) bound with high affinity (Kd: 5.33 nM) to a single site on the dopamine transporter and was selective for dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In PE2I studies, the cerebellum has been used as a reference region due to its negligible amount of DAT (Madras et al ., 1998; Hall et al ., 1999; Jucaite et al ., 2006). Because of this, one would expect the cerebellum to be described by a 1TC model, in which the one compartment represents free and nonspecifically bound ligand.…”
Section: Methodsmentioning
confidence: 99%
“…In PE2I studies, the cerebellum has been used as a reference region due to its negligible amount of DAT (Madras et al ., 1998; Hall et al ., 1999; Jucaite et al ., 2006). Because of this, one would expect the cerebellum to be described by a 1TC model, in which the one compartment represents free and nonspecifically bound ligand.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, levels in the cortex, including the PFC, are marginal. 44,45 In the human brain, MPH has been shown to occupy and block the DAT, 36,40,46,47 amplifying the DA signal. 35 Dopamine transporter blockade by MPH is dose dependent in the striatum.…”
Section: Blockade Of Datmentioning
confidence: 99%
“…This substantial improvement in sensitivity, especially near the center of the FOV, can play a key role in neuroreceptor imaging, particularly dynamic receptor imaging. The reduction in noise near the center of the FOV is crucial for precise measurement of binding potential, which is affected in Parkinson's disease and other movement disorders, 4,[11][12][13] as well as in attention deficit hyperactivity disorder. 14 The improvement in neuroreceptor imaging is obvious in the 123 I-altropane dopamine transporter study reported in this work; the striata were clearly visible with the SensOgrade collimator but not with the standard parallelhole collimator under the same imaging conditions, despite the fact that the latter offers sensitivity two to three times greater than that of a conventional dual-head SPECT camera.…”
Section: Discussionmentioning
confidence: 99%